Hyperthermia and hypercapnia following two intravenous injections of atracurium in a dog. Issue 1 (1st June 2015) - Rigotti, Clara; Dugdale, Alex; Alderson, Briony
Abstract : A three month old, 5 kg American Bulldog presented with severe dyspnoea and cyanosis seven hours after being submerged in a fresh‐water paddling pool. Oxygen was supplemented using an oxygen cage, but due to worsening of the clinical signs anaesthesia was induced with 2 mg/kg of propofol and the dog's trachea was intubated. Anaesthesia was maintained with a propofol infusion and mechanical ventilation was provided with 100 per cent inspired oxygen. As the patient was consistently hypercapnic and breathing against the ventilator, atracurium was administered intravenously at 0.2 mg/kg but five minutes later, the dog became hyperthermic (40°C) and hypercapnia drastically worsened. The hyperthermia and hypercapnia slowly resolved to pre‐atracurium values with active cooling. After three hours another dose of atracurium was administered and a similar hyperthermic and hypercapnic reaction developed. Due to the inability to effectively ventilate the lungs and the poor prognosis the owners elected for euthanasia.